A review of 2019 fuel cell technologies: modelling and controlling. (9th November 2020) - Pham, Thu Thi; Mollaamin, Fatemeh; Monajjemi, Majid; Dang, Chien Mau
Ion transport rates of direct forming acid (DFAFC), phosphoric acid (PAFC), alkaline (AFC), proton exchange membrane (PEMFC), direct methanol (DMFC) and solid oxide (SOFC) fuel cells have been studied. AFC which uses an aqueous alkaline electrolyte is suitable for temperature below 90° and is appropriate for higher current applications, while PEMFC is suitable for lower temperature compared to others. Not only are fuel cells clean energy for environment, but they can also have more than two times the efficiency of traditional combustion technologies. However, despite current developments, these technologies are not mature enough to be significantly into the energy market to replace petroleum. Hydrogen is an important energy carrier and a strong candidate for energy storage. It will be a useful tool for storing intermittent energy sources such as solar radiation. Hydrogen is a versatile energy carrier that can be used to power nearly every end-use energy need. By this work, modelling and controlling of ion transport rate efficiencies in PEMFC, AFC, DMFC, PAFC, DFAFC, direct carbon fuel cell (DCFC) and molten carbonate fuel cells (MCFC) have been investigated and compared. Thermodynamic equations have been investigated for those fuel cells from the viewpoint of voltage output data. Effects of operating data including temperature (T), pressure (P), proton exchange membrane water content (λ), and proton exchange membrane thickness (dmem ) on the optimal performance of the irreversible fuel cells have been studied. Performance of fuel cells was analysed via simulating polarisation and power curves for a fuel cell operating at various conditions with current densities.